Prinsip Strict Liability dalam Penyelesaian Sengketa Pencemaran dan Kerusakan Lingkungan Hidup Berbasis Keadilan: Studi Kasus PT Newmont Minahasa Raya - Nor Alfisyahr (Jurnal Hukum Lex Generalis, 2025)
Pollution and environmental damage are serious problems that require an effective and fair dispute resolution mechanism. The principle of strict liability or absolute responsibility is one of the important legal instruments in resolving environmental disputes in Indonesia. This study aims to analyze the implementation of the principle of strict liability in resolving pollution and environmental damage disputes in Indonesia and identify obstacles and challenges in its implementation. This research uses normative legal research methods with a statute approach, a case approach, and a theoretical approach. The results of the study show that the principle of strict liability has been regulated in Law Number 32 of 2009 concerning Environmental Protection and Management, but its implementation still faces various obstacles both in terms of proof, law enforcement, and awareness of business actors. This study recommends the need to strengthen the capacity of law enforcement officials, harmonize regulations, and increase legal awareness of the community and business actors to optimize the implementation of the principle of strict liability in resolving environmental disputes.